2001
DOI: 10.1063/1.1343476
|View full text |Cite
|
Sign up to set email alerts
|

Strong in-plane birefringence of spatially nanostructured silicon

Abstract: We report on a strong intrinsic optical anisotropy of Si induced by its dielectric patterning. As a result, an in-plane birefringence for nanostructured (110) Si surfaces is found to be 104 times stronger than that observed in bulk silicon crystals. We found the value of birefringence to be strongly dependent on the dielectric surrounding of the silicon nanoparticles assembling these layers. Beyond numerous potential implications for realization of optical devices and sensors, this gives a favorable route for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 12 publications
0
54
0
Order By: Relevance
“…This preferential pore alignment has an important implication for the optical properties of the layers [3]. Etched Si layers electrochemically formed on p-type Si (110) wafers reveal strong in-plane birefringence [1,2,3]. Birefringent etched Si layers demonstrate properties of a uniaxial negative crystal whose optical axis lies along the [001] in-plane crystallographic direction [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This preferential pore alignment has an important implication for the optical properties of the layers [3]. Etched Si layers electrochemically formed on p-type Si (110) wafers reveal strong in-plane birefringence [1,2,3]. Birefringent etched Si layers demonstrate properties of a uniaxial negative crystal whose optical axis lies along the [001] in-plane crystallographic direction [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been indicated that nanostructuring of Si by porousification of low-symmetry Si (110) surfaces or by formation of micrometer sized Si periodic structures is an appropriate technique for producing birefringent Si-based material [2]. The reduced symmetry of the dielectric function of etched Si layers originates from the selective pore dispersion in equivalent [100] crystallographic directions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, if H 1 = 0 then from (31), (30) and (22) we have that electric field keeps its components E 3 and E 2 . Combining (22) with (31) we obtained:…”
Section: Transverse Electric (Te) and Transverse Magnetic (Tm) Wavesmentioning
confidence: 99%
“…Transverse electric wave means E 3 = 0, then from (30)-(31) we have component H 1 = 0 and from (22) that E 2 = 0. On the other hand, if E 1 = 0 then from (33) and (32) we have that magnetic field keeps its components H 3 and H 2 .…”
Section: Transverse Electric (Te) and Transverse Magnetic (Tm) Wavesmentioning
confidence: 99%
See 1 more Smart Citation